Discretionary Accruals Earnings Management on Performance of Nigerian Listed Oil and Gas Companies - Abubakar, Aliyu; Suleiman-Ahmed, Hadiza (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study determines the impact of discretionary accruals earnings management on the financial performance of listed oil and gas companies in Nigeria. The study used panel data obtained from the annual reports and accounts of listed oil and Gas companies for a period of ten years (2013-2022). The dependent variable of the study is financial performance measured by return on assets (ROA), with leverage and liquidity as control variables. Panel regression was used to explore the effect and association of the dependent variable and two control variables (LEV and LIQ) with the independent variable discretionary accruals earnings management (DAEM), which were regressed using the EViews version 12 statistical package. The results obtained indicated the presence of earning management practices among the oil and gas managers. The managers manipulate the companies’ data in order to earn selfishly. The paper finally brings to the fore the modalities that the affected companies can take in order to stop the menace.